Examination of antimicrobial effect of fluoxetine in experimental sepsis model: An in vivo study. Issue 1 (10th October 2022) - Cakir, Ahsen; Bozali, Kubra; Celikten, Mert; Guler, Eray Metin; Sahan, Ebru; Durdu, Bulent; Sumbul, Bilge; Kocyigit, Abdurrahim
Abstract: Since most infectious diseases can develop into sepsis, it is still a major medical problem. Some in‐vivo studies showed promising properties of fluoxetine in the treatment of infections. This study aims the antimicrobial effect of fluoxetine on the inflammatory process used in the treatment of sepsis‐modeled rats. Besides, to investigate the efficacy of fluoxetine on modifying the antibiotic effect of imipenem in the inflammatory response. An experimental sepsis model was divided into negative control, positive control, fluoxetine 5 mg/kg, imipenem 60 mg/kg, and combined (fluoxetine; imipenem). Procalcitonin (PCT), high‐sensitivity C‐reactive protein (hs‐CRP), lactate, myeloperoxidase activity (MPO), the inflammation markers interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), tumor necrosis factor‐alfa (TNF‐α), and monocyte chemoattractant protein‐1 (MCP‐1) levels were measured by enzyme‐linked immunosorbent assay method. Oxidative stress markers, total oxidant status (TOS), total antioxidant status (TAS), total thiol (TT), and native thiol (NT) were measured using photometric methods. Oxidative stress index (OSI) was calculated according to TAS and TOS levels. The statistical analysis was performed by Statistical Package for Social Sciences version 22.0. After treatment with fluoxetine, imipenem, and combined groups, IL‐1β, IL‐6, TNF‐α, MPO activity, MCP‐1, hs‐CRP, PCT, lactate, and the oxidative stress markers OSI, and disulfide levels were decreased ( p < 0.05). The TT, NT, and TAS levels significantly statistically increased ( p < 0.05). This research demonstrates that fluoxetine has effects as anti‐inflammatory and antioxidant, and the combined treatment with antibioticum imipenem indicates positive synergistic effects in the experimental sepsis model.